What should be the treatment for intestinal neuronal dysplasia type B? A comparative long-term follow-up study - Lourenção, Pedro Luiz Toledo de Arruda [UNESP]; Ortolan, Erika Veruska Paiva [UNESP]; Rosa, Laura Luiza Minelli [UNESP]; Angelini, Marcos Curcio [UNESP]; Cassettari, Vanessa Mello Granado [UNESP]; Terra, Simone Antunes [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP] (Elsevier, 2020)
Purpose: To present the long-term follow-up outcomes of patients with intestinal neuronal dysplasia type B (IND-B) managed either conservatively or surgically. Methods: We conducted an ambispective, observational, longitudinal, and comparative study. Clinical data were reviewed at the start of treatment. After a minimum period of five years, the patients participated in semi-structured interviews in which the bowel function score (BFS) was applied to assess intestinal function, a proposed intestinal symptom index (ISI) to assess clinical symptoms, and a classification of clinical prognosis to assess treatment success. Comparisons between the two types of treatment were performed by evaluating pre- and post-treatment criteria. Results: Fifty patients diagnosed with IND-B were included in the study. Thirty-eight patients underwent surgical treatment (26 elective surgical treatment for primary colorectal resection and 12 emergency colostomies for intestinal obstruction or enterocolitis). Twelve patients were managed conservatively. With the exception of the patients who required an emergency operation (n = 12), the two groups were composed of patients with severe constipation who had similar clinical and functional characteristics at the time of IND-B diagnosis. A better clinical response was observed in patients submitted to conservative treatment, with a greater increase in the BFS (16.5 [-4/+18] versus 4 [-15/+17]; p = 0.001), indicating better bowel function and a more pronounced drop in ISI (-6 [-7/-4] versus -4 [-6/+1]; p = 0.015), suggesting fewer symptoms. The percentage of patients who had a successful treatment was higher in the group treated conservatively (72.7% versus 42.3%; p = 0.03). Conclusion: Conservative management showed better long-term outcomes than surgical management in children with IND-B.
Keywords: Child; Constipation; Enteric nervous system; Intestinal neuronal dysplasia type B